Lacrimal gland enlargement in inactive thyroid eye disease: a case series and literature review - Khan, Abdullah M.; Alawi, Abeer; Elkhamary, Sahar M.; Sheikh, Osama; Alsulaiman, Hamad M.; Khandekar, Rajiv; Schellini, Silvana A. [UNESP] (GN1 Sistemas e Publicacoes, 2024)
PURPOSE: This study aimed to evaluate the morphometric and volumetric dimensions of the lacrimal gland in patients with inactive thyroid eye disease and compare them with the values reported in the literature. METHODS: This case series evaluated consecutive patients with inactive thyroid eye disease treated at a tertiary eye hospital from 2015 to 2020. The patients' baseline demographics and clinical characteristics were obtained. The axial and coronal length, width, and volume of the lacrimal gland were measured on computed tomography scan images, and the results were statistically analyzed. RESULTS: A total of 21 patients (42 orbits) with inactive thyroid eye disease were evaluated. Their mean age was 49.0 ± 14.6 years, and 12 (57.1%) of them were men. The main complaint was dryness, and the majority of the patients had good vision and mild proptosis. The mean axial length and width of the lacrimal gland were 19.3 ± 3.9 mm and 7.5 ± 2.1 mm, respectively; coronal length and width, 20.4 ± 4.5 mm and 7.5 ± 2.1 mm, respectively; and lacrimal gland volume, 0.825 ± 0.326 mm3. Age, sex, or laterality were not found to be determinants of lacrimal gland enlargement. CONCLUSION: Patients with thyroid eye disease have enlarged lacrimal gland even in the nonactive phase of the disease multifactorial aspects influence the lacrimal gland in thyroid eye disease, making it difficult to establish a clear correlation with predisposing factors. Further studies are warranted to better understand the association between thyroid eye disease and the lacrimal gland.